Preventing Brain Damage from Hypoxic–Ischemic Encephalopathy in Neonates: Update on Mesenchymal Stromal Cells and Umbilical Cord Blood Cells - Nabetani, Makoto; Mukai, Takeo; Shintaku, Haruo (American Journal of Perinatology, 2021)
Neonatal hypoxic–ischemic encephalopathy (HIE) causes permanent motor deficit “cerebral palsy (CP),” and may result in significant disability and death. Therapeutic hypothermia (TH) had been established as the first effective therapy for neonates with HIE; however, TH must be initiated within the first 6 hours after birth, and the number needed to treat is from 9 to 11 to prevent brain damage from HIE. Therefore, additional therapies for HIE are highly needed. In this review, we provide an introduction on the mechanisms of HIE cascade and how TH and cell therapies such as umbilical cord blood cells and mesenchymal stromal cells (MSCs), especially umbilical cord-derived MSCs (UC-MSCs), may protect the brain in newborns, and discuss recent progress in regenerative therapies using UC-MSCs for neurological disorders.The brain damage process “HIE cascade” was divided into six stages: (1) energy depletion, (2) impairment of microglia, (3) inflammation, (4) excitotoxity, (5) oxidative stress, and (6) apoptosis in capillary, glia, synapse and/or neuron. The authors showed recent 13 clinical trials using UC-MSCs for neurological disorders.The authors suggest that the next step will include reaching a consensus on cell therapies for HIE and establishment of effective protocols for cell therapy for HIE.Key Points
Keywords: hypoxic–ischemic encephalopathy; cerebral palsy; umbilical cord blood stem cells; mesenchymal stromal cells; HIE; CP; MSCs; secondary energy failure